2017
DOI: 10.3390/ijerph14030242
|View full text |Cite
|
Sign up to set email alerts
|

Domain-Specific Self-Reported and Objectively Measured Physical Activity in Children

Abstract: Little is known about the extent that different domains contribute to total sedentary (SED), light (LPA) and moderate-to-vigorous physical activity (MVPA). We aimed to identify domain-specific physical activity (PA) patterns in school-aged children who were assessed by questionnaire and accelerometry. For the study, 298 German school children and adolescents aged 6–17 years wore an accelerometer for one week and completed a PA recall-questionnaire for the same period. Spearman coefficients (r) were used to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 38 publications
2
44
1
Order By: Relevance
“…Moreover, three-quarters of school time was spent in ST. As other studies have shown, the school setting accounts for high ST (Bailey et al 2012;Smith et al 2016;Sprengeler et al 2017), and girls in this study spent 3 h and 30 min sedentary during lesson hours. Huber and Köppel (2017) reported even 4.9 h of school-related ST across all grades.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, three-quarters of school time was spent in ST. As other studies have shown, the school setting accounts for high ST (Bailey et al 2012;Smith et al 2016;Sprengeler et al 2017), and girls in this study spent 3 h and 30 min sedentary during lesson hours. Huber and Köppel (2017) reported even 4.9 h of school-related ST across all grades.…”
Section: Discussionsupporting
confidence: 63%
“…Despite its limitations in the accurate recording of swimming and cycling, the use of accelerometers is preferable compared with that of questionnaires due to the poor validity of questionnaires, especially in the pediatric population 41 . Accelerometers also enable more accurate comparisons of different time segments of the day because the activities during some parts of the day may be underestimated, and others overestimated, by self‐report 42 …”
Section: Discussionmentioning
confidence: 99%
“…This was a retrospective study which analyzed data routinely provided by children with hemophilia and their parents over their last three clinic visits. The lack of a standardized collection method could have led to information bias in the data and potential overestimation of sports participation and underestimation of sports injuries 36,37 . Although no gold standard for self‐reporting of sports participation exists, using a standardized questionnaire as the Modifiable Activities Questionnaire (MAQ) 38,39 might be one way of improving sports participation assessment.…”
Section: Discussionmentioning
confidence: 99%